Suggestions for Digital Archives of Korean Christianity - So, John; Hwang, Byoung-Bae (International Journal of Engineering and Technology, 2019)
Â The purpose of this study is to assist researchers by making it quicker and easier to access data related to Korean Protestant history. The findings can be applied broadly to the field of Protestant history and will help researchers digitalize historical materials and study them systematically. The most important problem addressed in this study, in addition to the issue of storing and accessing data electronically, is the digitalization of historical data and the way in which electronic documents in humanities fields can reflect various types of information and data in a single document. We should classify the content of Korean Protestant historical data with this in mind. This study aims to create a fast and accurate research environment suited to the IT age through electronic archives that are well maintained and accessible to anyone. This paper also discusses ways of labelling primary sources to clearly differentiate dataâ€”in particular, by tagging search words in related major themes. Archives need to focus on mutual security, not one-sided support of researchers.Â